Gastric Pneumatosis: the tale of two late preterm infants with Necrotizing Enterocolitis - Belle Jarvis Shivon; Hughes Saleem; Richardson Claudine (International Journal of Neonatology, 2023)
Gastric pneumatosis though rare, when seen is cause for concern. It has been associated with fulminant necrotizing enterocolitis (NEC) and gastric outlet obstruction, although other associations have been identified. It is not to be confused with pneumoperitoneum and can be managed conservatively as it is not always a harbinger of intestinal perforation. This case report highlights gastric pneumatosis which occurred in association with necrotizing enterocolitis in two late preterm infants. NEC accounts for 5.4% of our Neonatal Intensive Care Unit admissions, however these are the first two cases of gastric pneumatosis seen in the history of our unit. It is crucial for clinical staff to be cognizant of this pathognomonic sign so that cases are not missed, and for the feeding policy that governs the management of late preterm infants to be revisited. That which specifically predisposes a baby with NEC to developing gastric pneumatosis remains unknown and warrants further research.
Keywords: Gastric Pneumatosis